Dose-Dependent Anti-Fibrotic Effect of Thymoquinone on Renal TGF-β1 Expression in Wistar Rats with Unilateral Ureteral Obstruction - M Zulfikar Abadi; Suprapti; Muhammad Irsan Saleh; Zulkhair Ali; Novadian (HM Publisher, 2026)
Background: Renal fibrosis is the final common pathway of chronic kidney disease (CKD), regulated by the pro-fibrotic cytokine Transforming Growth Factor-β1 (TGF-β1). Thymoquinone, the principal bioactive constituent of Nigella sativa, has antioxidant, anti-inflammatory and anti-fibrotic activity in pre-clinical models, but its dose-response profile in obstructive nephropathy is incompletely characterised. Methods: This in-vivo experimental study used a post-test-only with control-group design in 30 male Wistar rats (200–250 g) randomised into six groups (n=5): sham + olive-oil; UUO + olive-oil; UUO without olive-oil; and UUO with intra-peritoneal thymoquinone at 5, 10 or 20 mg/kg body-weight daily for 14 days. The primary outcome was renal cortical TGF-β1 mRNA expression by RT-PCR; secondary outcomes were IL-6 expression, serum urea and creatinine, Sirius-red percentage of positively-stained area (PSA) and a PAS-stained tubular injury score. Results: UUO produced renal injury: urea rose from 41.3 ± 6.2 to 57.7 ± 7.6 mg/dL (p=0.003) and TGF-β1 expression rose from 473,500 ± 32,797 to 679,922 ± 27,998 densitometric units (p=0.001). Thymoquinone reduced TGF-β1 dose-dependently to 644,571 ± 25,457, 612,143 ± 23,822 and 581,571 ± 24,128 a.u. at 5, 10 and 20 mg/kg (ANOVA p=0.004); the 20 mg/kg dose was superior to lower doses (p<0.05). PSA and tubular injury improved in parallel and correlated strongly with TGF-β1 (r=0.85). Conclusion: Thymoquinone exerts a dose-dependent anti-fibrotic effect via TGF-β1 down-regulation in obstructive nephropathy, supporting its evaluation as a complementary anti-fibrotic adjunct in CKD.